ANALISIS SIFAT KIMIA FISIK FLUIDA DAN ESTIMASI TEMPERATUR RESERVOIR DI DAERAH MANIFESTASI PANAS BUMI BAKAN BOLAANG MONGONDOW - Marcelino Datunsolang; Cyrke Bujung; Jeferson Polii (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
Bolaang Mongondow is an area that has an active volcano, namely the Ambang volcano, which is located in the village of Bakan. The existence of hot spring manifestations that appear indicates the potential for geothermal energy in the area. However, until now, geothermal potential in the area has not been developed due to a lack of knowledge about determining geothermal potential. For this reason, research on reservoir characteristics such as fluid type and reservoir temperature estimation is carried out. The method used in this research is the geochemical analysis of the fluid in the form of the percentage of fluid content and the calculation of the geothermometer. Fluid type analysis was determined based on plotting on ternary Na-K-Mg diagrams. While the reservoir temperature estimation is determined using the Na-K geothermometer equation. From the physical-chemical analysis of fluids in Bakan hot springs, it was found that the type of fluid in the Bakan area was immature water. Based on the estimated reservoir temperature calculation using a Na-K Geothermometer, the subsurface temperature ranges from 235 ℃ - 242 ℃ and includes a High-temperature reservoir.